An Investigation of Electrospun Clerodendrum phlomidis Leaves Extract Infused Polycaprolactone Nanofiber for In Vitro Biological Application - Siranjeevi Ravichandran; Rajesh Jegathaprathaban; Jeyalakshmi Radhakrishnan; R. Usha; V. Vijayan; Aklilu Teklemariam (Bioinorganic Chemistry and Applications)
The in vitro antibacterial, anticancer, and antioxidant activities of a few plant extracts were widely known for decades, and they were used for application in the conventional way. Specifically, electrospun nanofibrous mats have recently exhibited great antibacterial, anticancer, and antioxidant activities. The herbal extracts infused into these formations are expected to have a more efficient and integrated effect on in vitro biological applications. The purpose of this study is to develop polycaprolactone- (PCL-) based nanofiber mats that are infused with a traditional plant extract using Clerodendrum phlomidis leaves to improve the synthesized nanofibers’ antibacterial, anticancer, and antioxidant efficacy. This study examined the morphology, thermal properties, mechanical properties, structure, and in vitro drug release studies of electrospun nanofibers. Antibacterial, anticancer, and antioxidant activities of the electrospun nanofibrous mats were also studied. The HRTEM and FESEM pictures of PCL and PCL-CPM nanofibers provide that smooth, defect-free, and homogeneous nanofibers were found to be 602.08 ± 75 nm and 414.15 ± 82 nm for PCL and PCL-CPM nanofibers, respectively. The presence of Clerodendrum phlomidis extract in the electrospun nanofibers was approved by UV-visible and FTIR spectroscopy. The incorporation of Clerodendrum phlomidis extract to nanofiber mats resulted in substantial antibacterial activity against bacterial cells. PCL-CPM mats exposed to oral cancer (HSC-3) and renal cell carcinoma (ACHN) cell lines displayed promising anticancer activity with less than 50% survival rate after 24 h of incubation. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay performed on PCL-CPM nanofibers revealed the antioxidant scavenging activity with maximum inhibition of 34% suggesting the role of the secondary metabolites release from scaffold. As a result, the findings of this study revealed that Clerodendrum phlomidis extract encapsulating PCL electrospun nanofibers has a high potential for usage as a biobased antibacterial, anticancer, and antioxidant agent.